Gender, Poverty, and Nonfarm Employment in Ghana and Uganda - Newman, Constance; Canagarajah, Sudharshan (World Bank, Washington, DC, 2015)
The authors provide evidence that women's non-farm activities help reduce poverty in two economically and culturally different countries, Ghana and Uganda. In both countries rural poverty rates were lowest - and fell most rapidly - for female heads of household engaged in non-farm activities. Participation in non-farm activities increased more rapidly for women, especially married women and female heads of household, than for men. Women were more likely than men to combine agriculture and non-farm activities. In Ghana it was non-farm activities (for which income data are available ) that provided the highest average incomes and the highest shares of income. Bivariate profit analysis of participation shows that in Uganda female heads of household and in Ghana women in general are significantly more likely than men to participate in non-farm activities and less likely to participate in agriculture.